Patient safety, patient safety culture, medical errors and adverse events: Review - Gürkan Kapıkıran; Semra Bülbüloğlu; Fatma Eti Aslan (Association of Nurse Managers, 2018)
Recent studies shows that patient safety in the operating room sometimes has neglected due to system based, organizational, health care working. But patient safety an essential component for perioperative nursing. The aim of this study prepared institutions for dedicated patient safety while proving health care all the perioperative processes. Perioperative nurses a member of multidisciplinary team report to preserving dignity and comfort, preventing possible mistakes, making advocacy the patient, submitting a modern health care all the perioperative processes. Therefore it may to mention of setting on environment in the operating room, equipment ready for use, to prevent medical errors and adverse events, application of aseptic teqniques and so on.